TALIBAN OR TERRORIST? SOME REFLECTIONS ON TALIBAN’S IDEOLOGY - Sultana, Aneela (2009)
This article reflects religious, political and cultural foundations of Taliban’s creed which makes them different in the Islamic world as well as gives them special place in today’s international power politics. The main objective of this article is to review Taliban’s policies which are manifested frequently in their public statements and general practices. It further explains the influence of tribal customs and traditional Pushtun code of conduct over the establishment of Taliban’s movement. An attempt is made to appraise gender policy of Taliban’s which dictates strict moral code for both men and women and its repercussions for gender relations. This paper also discusses all those factors which contributed in the rise of talibanization in Afghanistan as well as in other parts of the Muslim world. Madrassa education is strongly believed to be responsible for designing terrorist minds. This article reveals views of talibs (madrassa students) regarding the nature of their studies and the way this knowledge is actually applied in the course of their life.
Keywords: Ideology; Politics; Religion; Taliban; Terrorism; Tribal Customs